An explicit estimation of exponential sum associated with a quintic form - Mohd Atan, Kamel Ariffin (2012)
It has been shown that the estimation of an exponential sum associated with a two-variable polynomial can be derived from the estimation of the cardinality of the set of common solutions to congruence equations associated with the partial derivatives of the polynomial. By an application of this principle we will present in this talk a method of determining an exponential sum associated with a quintic of the form